2019
DOI: 10.1371/journal.pone.0211514
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine responses and food intake in fasted individuals under the influence of glucose ingestion

Abstract: IntroductionDifferent metabolic conditions can affect what and how much we eat. Hormones of glucose metabolism and adipokines such as adiponectin take part in the control of these decisions and energy balance of the body. However, a comprehensive understanding of how these endocrine and metabolic factors influence food intake has not been reached. We hypothesised that the amount of food a person consumes differs substantially after a fasting period even after the energy deficit was partially removed by glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
4
1
Order By: Relevance
“…Short-term part of the present study reported continued reduction until the ad-libitum lunch for both Pla and Lc-Hs. Meanwhile, previous studies have seen an increase in adiponectin (51). Therefore, the variation of adiponectin in the present study seems to be in uenced in both short and long periods, showing different trends.…”
Section: Discussioncontrasting
confidence: 64%
“…Short-term part of the present study reported continued reduction until the ad-libitum lunch for both Pla and Lc-Hs. Meanwhile, previous studies have seen an increase in adiponectin (51). Therefore, the variation of adiponectin in the present study seems to be in uenced in both short and long periods, showing different trends.…”
Section: Discussioncontrasting
confidence: 64%
“…Various studies have suggested that protein ingestion, resulting in increases in plasma concentrations of essential and nonessential amino acids, promotes insulin and glucagon secretion 27,33,34 . The literature also reports compensatory increases in energy intake after a period of caloric restriction, despite PO administration of glucose, as opposed to nonfasted individuals 35 . This finding suggests that proteins, fatty acids, or other components of mare's milk could have stimulated or enhanced glucagon secretion when the foals in our study nursed.…”
Section: Discussionsupporting
confidence: 54%
“…27,33,34 The literature also reports compensatory increases in energy intake after a period of caloric restriction, despite PO administration of glucose, as opposed to nonfasted individuals. 35 This finding suggests that proteins, fatty acids, or other components of mare's milk could have stimulated or enhanced glucagon secretion when the foals in our study nursed. Future investigations to further evaluate mechanisms involved in the hyperglucagonemic response to nursing observed in our study should include identifying which components of mare's milk have the ability to stimulate the endocrine pancreas, and assessment of the energy axis in the healthy foal in response to administration of various amino acids, such as L-arginine.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Short-term part of the present study reported continued reduction until the ad-libitum lunch for both Pla and Lc-Hs. Meanwhile, previous studies have seen an increase in adiponectin [ 66 ]. Therefore, the variation of adiponectin in the present study seems to be influenced in both short and long periods, showing different trends.…”
Section: Discussionmentioning
confidence: 99%